Qualitative study of patients’ and clinicians’ experiences of an educational intervention for warfarin therapy control in atrial fibrillation in Thailand - Kate Jolly; Jonathan Mathers; Arintaya Phrommintikul; Gregory YH Lip; Chaisiri Angkurawaranon; Rungroj Krittayaphong; Deirdre Lane; Wichuda Jiraporncharoen; Nida Buawangpong; G Neil Thomas; Surakit Nathishuwan (BMJ Open)
Objectives We aimed to understand the (1) perspectives of patients with atrial fibrilation (AF) regarding their experience and implementation of The SAMe-TT2R2 score-guided approach in anticoagulant-nave Thai patients with atrial fibrillation (TREATS-AF) educational intervention for warfarin therapy control, including views on cultural transferability to the Thai context, and (2) healthcare professionals’ (HCPs) experience of implementing the intervention.Design Qualitative research study.Setting Three university hospitals and four tertiary care hospitals in Thailand.Participants 13 newly diagnosed patients with AF and 13 HCPs delivering the TREATS-AF intervention, an intensive structured educational programme.Methods Semistructured interviews. Patient participants were interviewed at two time points: 4 weeks and 6 months after intervention delivery. HCPs were interviewed when they had at least 6 months experience of intervention delivery. A thematic analysis of content was informed by the framework analytical approach.Results 13 patients and 13 HCPs were interviewed; most were female (73.3% of patients and all HCPs). Mean age was 70 (68–76) and 40 (38–42.5) years for patients and HCPs, respectively. There were four categories related to the experience of the TREATS-AF intervention: (1) key experiences of the educational sessions, (2) core perceptions of the educational materials provided, (3) suggestions for improving the educational materials and session, and (4) behavioural change and self-management influenced by the TREATS-AF intervention.Conclusions The TREATS-AF intervention assisted interviewees who were newly diagnosed with AF in preparing themselves with the necessary knowledge and skills to manage their condition. They stated that it increased their confidence in self-management.For implementation, regionalised Thai-related food and beverages, patients' literacy and family support should be considered, and infrastructure support for widespread use in healthcare settings would be required.Trial registeration number TCTR20180711003.